Legal regulation of commercial activities of Ukrainian airlines in implementation of international flights - Зуєва, Вікторія Олександрівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2012)
This article defines legal regulation basic principles of international airlifts carried out by Ukrainian airlines. The author concludes that at current stage of development of the legal regulations of Ukrainian airlines commercial activities the national legislation priority is to lead the rates of the Ukrainian law in accordance to the international flight safety standards.